Tax Planning, Earnings Management, and the Differential Information Content of Bank Earnings Components - Terry D. Warfield; Thomas J. Linsmeier (The Accounting Review, 1992)
[This research examines the information content of the bank earnings components entitled "Securities Transactions Gains and Losses" (STGL). STGL reflect the accounting gain or loss that arises when a bank sells an investment security at a price different from the book value. Institutional as well as anecdotal evidence suggests that investors may price STGL differently from the operating earnings component entitled "Income before Securities Transactions" (IBST). For example, prior to 1983, bank regulators viewed the IBST and STGL components as reflecting unique aspects of bank activities and, therefore, required that total bank earnings be disaggregated into IBST and STGL components (SEC 1983). In addition, because of investment market volatility and the discretionary nature of investment securities sales, STGL may convey limited information about current changes in bank value (Linden 1990). Indeed, with banks, security analysts often focus on IBST (Barth et al. 1990), and managers have been accused of selectively selling appreciated investment securities to increase reported levels of accounting earnings (Berton 1991; Wyatt 1991). Research by Barth et al. (1990) has assessed the relative ability of the IBST and STGL income components to explain cross-sectional variation in annual common stock prices. They predicted, for many of the reasons cited above, that the STGL earnings/security price multiple should be less than the multiple assigned to the IBST component. Their results confirm this prediction: IBST played an important role in explaining bank stock prices, but the earnings/security price multiple assigned to STGL did not differ significantly from zero. There are several reasons why STGL might not have exhibited information content in this research. First, as Barth et al. suggest, the incremental information content of the STGL component may have been diminished because STGL appear to be realized to smooth income. In this situation, STGL are likely to provide little incremental information about changes in bank equity values. Second, Barth et al. measure stock returns over a 12-month interval corresponding to the bank's fiscal year. When returns are measured over such a long period, the likelihood increases that information unrelated to earnings will also be reflected in equity prices, thereby (potentially) reducing the ability of earnings to explain security returns. Third, significant tax-related, cross-sectional differences may exist in the STGL earnings component/security price relationship, and these are "averaged away" when one overall earnings/security price coefficient is estimated. For example, Scholes et al. (1990) suggest that STGL may be realized to minimize taxes. Based on this tax-planning scenario (described in section I), security transaction losses (gains) for tax-paying (non-tax-paying) banks are predicted to be negatively (positively) related to bank equity values. The objective of this study is to assess whether the STGL earnings component is priced by investors in a manner consistent with this tax-planning rationale. Empirical tests measure the market reaction to IBST and STGL earnings information over the two-day interval consisting of the day before and day of the preliminary quarterly earnings release, and the results provide evidence that STGL are priced by investors in a manner consistent with the tax-planning hypothesis. However, these results appear to hold only in the first three quarters of the fiscal year. In the fourth quarter, there is no evidence that the STGL component is priced by bank investors. These fourth-quarter results are consistent with an increase in earnings-management activity related to STGL near the fiscal year-end]